Comprehensive identification of NRG1 fusions in 25,203 patients with solid tumors - Shui Xiang; Yiwen Zheng; Mengxiao Wang; Xuewen Liu; Xing Zhang; Dongsheng Chen; Guangxian Meng; Hongtao Xu; Xiaoxuan Wang (npj Precision Oncology)
Abstract NRG1 fusion is an emerging oncogenic driver, and the FDA has approved drugs for the treatment of non-small cell lung cancer and pancreatic cancer associated with NRG1 fusions. This study retrospectively analyzed data from 25,203 patients with solid tumors who underwent next-generation sequencing (NGS) and identified 49 patients with NRG1 fusions. The mutation profiles and actionable therapeutic targets were analyzed among patients with fusions. In this study, 0.2% (49/25,203) of patients harbored NRG1 fusions. The frequencies of NRG1 fusions across various cancer types were as follows: prostate cancer, 0.65%; breast cancer, 0.47%; lung cancer, 0.29%; esophageal cancer, 0.25%; colorectal cancer, 0.17%; gastric cancer, 0.13%; pancreatic cancer, 0.11%; and hepatocellular carcinoma, 0.05%). A total of 36 fusion partners were detected, among which CD74 was predominant, accounting for 29.3% of cases. Patients with NRG1 fusions presented a greater frequency of FGFR1 mutations and RET fusions, compared with non-NRG1 fusion patients. Most lung cancer and colorectal cancer patients with NRG1 fusions harbored FDA-approved or potential drug targets, whereas those diagnosed with breast cancer harbored fewer such targets. NRG1 fusion-related drugs can provide additional treatment options. Our study expands the NRG1 fusion gene landscape and provides a valuable reference for the comprehensive treatment of patients with NRG1 fusions.